An Exploratory Study on Effects of WeChat-Assisted Self-Regulated English Writing Instruction on EFL Learners’ Motivation (International Conference on Computers in Education, 2023)
Scholars suggested using social networking to assist second language and foreign language learning. Researchers in the present study designed and developed a Mini Program on the WeChat platform to assist university EFL learners in improving self-regulated English writing. This exploratory study aims to investigate the effects of WeChat-assisted Self-Regulated English Writing Instruction on university EFL learners’ motivation in English writing. A quasi-experimental design with forty-five second-school-year university students was conducted for two weeks. Participants were randomly divided into the control group, the traditional group and the WeChat-assisted group. They took a pre- and post-questionnaire survey on English writing motivation before and after the intervention. Descriptive statistic analysis was used to show the status quo of the participants’ motivation, paired sample t-test was used to analyze the differences in motivation within each group before and after the intervention, and ANOVA analysis was used to compare differences in motivation between groups after the intervention. Both the traditional approach and the WeChat approach generated positive impacts on students’ overall motivation, self-efficacy and interest. Students using the traditional approach outperformed those using the WeChat-assisted approach but the results did not reach a significant level. Implications for future studies are suggested.